2017
DOI: 10.1371/journal.pone.0178300
|View full text |Cite
|
Sign up to set email alerts
|

Level of surgical experience is associated with change in hip center of rotation following cementless total hip arthroplasty: A radiographic assessment

Abstract: ObjectivesAfter total hip arthroplasty (THA), restoration of hip center of rotation (COR) is essential to ensure stability of the prosthetic hip and longevity of the prosthesis. Our aim was to determine whether, and how, the COR changed postoperatively compared to the native COR following implantation of a cementless acetabular component in anatomical position and to compare the accuracy of cup placement between two surgeons with different levels of surgical experience.Materials and methodsWe evaluated 145 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 31 publications
2
25
0
Order By: Relevance
“…Several studies reported the significant differences in the radiographic and clinical outcomes between surgeons with different levels of surgical expertise, such as change in the COR, initial cup position, cup orientation, number of cups within the safe zones, and dislocation rate. The percentage of hips located within the safe zones varies from 70.5 to 25.7% [1113, 17]. In the present study, patients using this positioner have less vertical displacement of the COR of the hip when compared with those in group B.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Several studies reported the significant differences in the radiographic and clinical outcomes between surgeons with different levels of surgical expertise, such as change in the COR, initial cup position, cup orientation, number of cups within the safe zones, and dislocation rate. The percentage of hips located within the safe zones varies from 70.5 to 25.7% [1113, 17]. In the present study, patients using this positioner have less vertical displacement of the COR of the hip when compared with those in group B.…”
Section: Discussionmentioning
confidence: 52%
“…However, RCH is not a definite anatomical structure, and its position rests with variables of acetabular cup depth, height, and angular position (anteversion and inclination) [9, 10]. These variables are able to be obtained on the postoperative X-ray of CT via many kinds of ways, but the methods that help to definite the position of RCH during surgery are seldom, mainly relying on experience of the surgeon, which attributes to great differences of accuracy rate of RCH between different medical centers [1113]. So a simple, reproducible, and affordable method is needed to resolve the problem.…”
mentioning
confidence: 99%
“…Accurate restoration of hip rotation center is one of the main factors affecting the stress distribution between the prosthesis interface, the prosthesis-bone interface, and the soft tissue around hip joint. Improper position of hip rotation center will result in polyethylene wear, prosthesis loosening, lameness, and other complications [11]. The anatomical restoration of hip rotation center can make uniform stress distribution of the prosthesis, recover the soft tissue tension, extend the survivorship of the prosthesis, and reconstruct the function of the hip joint to the maximum extent, which will improve the patients' satisfaction and clinical therapy effect [12].…”
Section: Discussionmentioning
confidence: 99%
“…The abduction and anteversion angles of the acetabular component, center of rotation (COR) in the horizontal and vertical planes [17], femoral/hip offset [17], and leg-length discrepancy (LLD) were measured as radiographic parameters after THA on 3-month standardized radiographs. Intraclass correlation coefficient values for intra-rater and inter-rater reliability were demonstrated to be excellent (all > 0.85) for these parameters in our previous studies [17, 18]. We used the method described by Lewinnek et al [19, 20] for the measurement of anteversion.…”
Section: Methodsmentioning
confidence: 99%